2010
DOI: 10.1007/s11136-010-9816-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal dental anxiety on oral health–related quality of life of preschool children

Abstract: Mean ECOHIS total score was not influenced by maternal dental anxiety. However, anxiety had a negative effect on the perception of the impact of the child's oral health problems in the family, affecting the parent distress domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
109
4
21

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(150 citation statements)
references
References 30 publications
(41 reference statements)
16
109
4
21
Order By: Relevance
“…A previous study found that anterior open bite was negatively associated with the function domain, according to the perception of parents. 24 Moreover; parents of children with anterior open bite are more likely to categorize the oral health of their child as poor. 25 The evaluation of how oral health problems impact OHRQoL should be made with validated measures and detailed methods.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that anterior open bite was negatively associated with the function domain, according to the perception of parents. 24 Moreover; parents of children with anterior open bite are more likely to categorize the oral health of their child as poor. 25 The evaluation of how oral health problems impact OHRQoL should be made with validated measures and detailed methods.…”
Section: Discussionmentioning
confidence: 99%
“…OHRQoL indices show buccal and dental disorders can impair social, psychological and physical activities, and disturb children's functional performance such as eating and speaking, psychological performance such as showing teeth and smiling without embarrassment, and social performance by damaging their social life [9,[11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…21 In this age group, the early development of dental caries is considered a public health problem, due to its high prevalence and because it affects the individual's quality of life. 11 The relationship between individual determinants and different health conditions, dental caries among them, is infl uenced by the context in which the individuals dwell. 10 Previous studies have discussed the occurrence of these health problems as being related to a complex causal network which includes determinants related to individual characteristics and the social and geographical context in hierarchically organized levels.…”
mentioning
confidence: 99%